Results from an Obesity Model in White Male Wistar Rats After Administration of Telang Flower (Clitoria Ternatea) Extract on Pancreatic Function and Histopathological Characteristics - Yulisandra Rini, Weni; Azmi Tanjung, Fahrul; Wilvia, Wilvia (CV. Inara, 2024)
Diabetes mellitus (DM) is a chronic disease affecting 95% of diabetics, characterized by high blood glucose levels due to decreased insulin production. Bioactive chemicals from plants like butterfly pea flower and Clitoria Ternatea can potentially treat DM, inhibit carbohydrate-digesting enzymes, and potentially regenerate pancreatic beta cells. This study tests butterfly pea flower extract on obesity-related pancreatic function in white rats. In obese rats given varied dosages of butterfly pea flower extract, the study evaluates pancreatic tissue histopathology and ethanol extract properties. The study examines male Wistar rats' acclimatization before treatment with butterfly pea flower extract, a high-fat diet, and butterfly pea flower extract, comparing the effects of the extract on rats. Pancreatic function is examined using enzymes amylase and lipase. Histopathological observation of pancreatic organs involves several steps, including fixation, washing, infiltration, embedding, cutting, attaching, deparaffinization, dealcoholization, staining, mounting, and scoring. A post-test-only control group design compared butterfly pea flower extract and pancreatic function in male white rats. Butterfly pea flower extract improved pancreatic histology in obese white rats at 600mg/KgWB, closer to the normal group. The extract contains secondary metabolites that repair cell tissue damaged by the rats' high-fat diet and obesity.